Swing - Alexander, Kwame; Hess, Mary Rand (Blink, 2018)
"Noah and his best friend Walt want to become cool, make the baseball team, and win over Sam, the girl Noah has loved for years. When Noah finds old love letters, Walt hatches a plan to woo Sam. But as Noah's love life and Walt's baseball career begin, the letters alter everything"--